Efektivitas Pembelajaran Online Mata Kuliah Filsafat Pendidikan Menggunakan Google Classroom di Masa Pandemi Covid-19 - Metoddyus Tri Brata Role; Apri Kurniawan; Theresia Yovita Cendana Sari (Jayapangus Press, 2022)
This research was conducted to test the effectiveness of online learning using google classroom in terms of student achievement and independence. This research is a quasi experimental study with the one group pretest posttest design. The research was conducted in the Educational Philosophy course, students were given a pretest of learning achievement and learning independence before learning was carried out using google classroom. After being given treatment, students were measured their learning achievement and independence. Learning achievement was measured using tests, while student independence was measured using independence questionnaires. After being measured, the data were analyzed. Learning is said to be effective if (1) the average student learning achievement score is more than 63 and the student independence score is more than 70, (2) more than 75% of students who get a minimum grade of B and enter the high criteria for student learning independence, and (3) the average posttest score is better than the pretest both for learning achievement and learning independence. Criteria (1) used the one sample t test, criteria (2) used the proportion test, while for criteria (3) used the paired sample t test. After analyzing data, online learning using google classroom is said to be effective in terms of learning achievement but not effective in terms of student independence.